The Mre11-Rad50-Xrs2 Complex Is Required for Yeast DNA Postreplication Repair - Ball, Lindsay G.; Hanna, Michelle D.; Lambrecht, Amanda D.; Mitchell, Bryan A.; Ziola, Barry; Cobb, Jennifer A.; Xiao, Wei (PLOS ONE, 2014)
Yeast DNA postreplication repair (PRR) bypasses replication-blocking lesions to prevent damage-induced cell death. PRR employs two different mechanisms to bypass damaged DNA, namely translesion synthesis (TLS) and error-free PRR, which are regulated via sequential ubiquitination of proliferating cell nuclear antigen (PCNA). We previously demonstrated that error-free PRR utilizes homologous recombination to facilitate template switching. To our surprise, genes encoding the Mre11-Rad50-Xrs2 (MRX) complex, which are also required for homologous recombination, are epistatic to TLS mutations. Further genetic analyses indicated that two other nucleases involved in double-strand end resection, Sae2 and Exo1, are also variably required for efficient lesion bypass. The involvement of the above genes in TLS and/or error-free PRR could be distinguished by the mutagenesis assay and their differential effects on PCNA ubiquitination. Consistent with the observation that the MRX complex is required for both branches of PRR, the MRX complex was found to physically interact with Rad18 in vivo. In light of the distinct and overlapping activities of the above nucleases in the resection of double-strand breaks, we propose that the interplay between distinct single-strand nucleases dictate the preference between TLS and error-free PRR for lesion bypass.